EDAD Y PALEOAMBIENTE DE LA "SERIE DEL YESO", VALLE DEL CURA, PROVINCIA DE SAN JUAN: EVIDENCIAS PALINOLÓGICAS (Ameghiniana, 2014)
A diverse and well preserved palynological assemblage is reported for the first time from the Upper section of the "Serie del Yeso", San Juan province, Argentina. The assemblage is dominated by herbaceous and shrubby forms of the families Cyperaceae, Poaceae, Malvaceae, Sympocaceae, Asteraceae, Anacardiaceae and Ephedraceae which, on sedimentological and palynological grounds, may have developed in the surroundings of a lacustrine environment. Tree components and fems are very sparse. Fresh water algae, mainly Botryococcus, are abundant. A few dinoflagellate cysts and acritarchs are present in thisassemblage which may suggest brackish conditions in the lake. The great development of gypsum seams in the Upper Section of the "Serie del Yeso" is in accord with this assumption. The spore-pollen assemblage suggests warm to warm temperate and dry climate conditions. This assemblage also suggests a Miocene age for this unit, probably Middle Miocene. A new combination, Mutisiapollis viteauensis (Barreda) Barreda combo nov., is here proposed. Cyperaceaepollenites neogenicus Krutzsc 1970 and Tetracolporites spectabilis Pocknall and Mildenhall 1984 are reported for the first time from Argentina.